Konsep Reconnecting With Nature pada Desain Hospitality Banyan Tree Escape - Primadewi , Siluh Putu Natha; Idedhyana, Ida Bagus; Rijasa, Made Mariada (Nature: National Academic Journal of Architecture, 2024)
Banyan Tree Escape is located in Payangan Gianyar Bali and has a unique design concept "no wall, no door" which is rarely found in other hospitality properties. This hospitality accommodation is designed to establish a harmonious relationship between the owner and guests and re-establish the relationship between humans and the natural environment, resulting in friendly service and a pleasant atmosphere. The hospitality industry requires the presence of nature, repeated and continuous engagement with nature is very important, creating an atmosphere of relaxation that can reduce stress and provide a new sense of healthy wellness. Incorporating nature and culture into property design in the hospitality industry also aims to achieve the Sustainable Development Goals. This research aims to examine concepts that can be applied to achieve a connection with nature and sustainability goals in hospitality design. The descriptive qualitative method of case study is used in this research, guided by the concept of Reconnecting with Nature for Sustainability, followed by Biodiversity Inclusive Design analysis, Nature Climate analysis, and Vernacular Lifestyle analysis. The results show that the concept of the Biodiversity Inclusive Design approach is carried out by maintaining the condition of biodiversity, imitating the characteristics of the original/local habitat (the original habitat of Buahan Village), and the application of biophilic architecture. The concept of natural climate is applied with a combination of tropical architecture and local architecture. The Vernacular Lifestyle concept is carried out by adopting the cultural context and traditional Balinese architecture in responding to routine and boredom into relaxation.